(untitled) (Discourse of Law and Administration, 2022)
The article concerns the evolution of the statutory framework of the freedom of scientific research and, more broadly, the freedom of science. The transformations of the system of higher education and science do not change the understanding, based on article 73 of the Constitution, of the content of the freedom of science in the doctrine of constitutional law which has a legal-natural origin. This study does not argue with the existing understanding of this freedom. I note, however, that in the last dozen or so years the exercise of this freedom has encountered new challenges connected with the requirements concerning the effectiveness of research or its connection with the financing of the university. The creative effort of the researcher is increasingly subordinated to the research teams and the development prospects of the scientific institution. The framework of research freedom has not changed, but the actual area of the researcher’s free decision is smaller. These circumstances may prompt us to think about the need for a new approach to identifying the causes of the limitations of scientific freedom, as well as to guarantee an appropriate level of research independence in the new institutional realities.